2019
DOI: 10.1093/brain/awz370
|View full text |Cite|
|
Sign up to set email alerts
|

The coding and non-coding transcriptional landscape of subependymal giant cell astrocytomas

Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominantly inherited neurocutaneous disorder caused by inactivating mutations in TSC1 or TSC2, key regulators of the mechanistic target of rapamycin complex 1 (mTORC1) pathway. In the CNS, TSC is characterized by cortical tubers, subependymal nodules and subependymal giant cell astrocytomas (SEGAs). SEGAs may lead to impaired circulation of CSF resulting in hydrocephalus and raised intracranial pressure in patients with TSC. Currently, surgical resection and mTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 90 publications
(139 reference statements)
1
24
0
Order By: Relevance
“…Indeed, human tuber and SEGA tissue also display activation of inflammation in astrocytes, in particular, the toll-like receptor 4 (TLR-4), interleukin 1β (IL-1β), and complement pathways, as well as increased expression of IL-17, intercellular adhesion molecule 1, tumor necrosis factor α (TNF-α), and nuclear factor κB (NF-κB) ( 61 63 , 96 98 ). In particular, several large-scale RNA-sequencing studies confirmed that neuroinflammation is a hallmark of TSC-associated lesions, and the retrieved data were enriched for both astrocyte and microglial specific genes ( 21 , 63 , 99 , 100 ). Additionally, microRNAs (miRNAs) involved in the regulation of astrocytic inflammatory responses are upregulated in TSC ( 101 ).…”
Section: Astrocytesmentioning
confidence: 93%
“…Indeed, human tuber and SEGA tissue also display activation of inflammation in astrocytes, in particular, the toll-like receptor 4 (TLR-4), interleukin 1β (IL-1β), and complement pathways, as well as increased expression of IL-17, intercellular adhesion molecule 1, tumor necrosis factor α (TNF-α), and nuclear factor κB (NF-κB) ( 61 63 , 96 98 ). In particular, several large-scale RNA-sequencing studies confirmed that neuroinflammation is a hallmark of TSC-associated lesions, and the retrieved data were enriched for both astrocyte and microglial specific genes ( 21 , 63 , 99 , 100 ). Additionally, microRNAs (miRNAs) involved in the regulation of astrocytic inflammatory responses are upregulated in TSC ( 101 ).…”
Section: Astrocytesmentioning
confidence: 93%
“…The precise role of T-cells in SEGAs is still unknown, it could indicate a more responsive immune response to tumor cells but we also know that, neuroin ammation can increase the expression and activity of MMPs, which are increased in SEGAs and can play a role in tumorgenesis (Bongaarts et al 2020). The MAPK pathway has been shown to be an important pathway for SEGA growth and has been suggested as a novel target for therapy for patients with SEGA (Bongaarts et al 2019, Tyburczy et al 2010, Mi et al 2009). Therefore, the differences in methylation of this pathway between the two groups found in this study is interesting and could potentially re ect how these tumors would respond to MAPK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Data was processed as previously described (Bongaarts et al 2019). Brie y, sequence reads were trimmed and ltered using FastQC v0.11.5 (Babraham Institute, Babraham, Cambridgeshire, UK) and Trimmomatic v0.36 (Bolger, Lohse, and Usadel 2014).…”
Section: Rna Isolation and Rna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…This group includes subependymal giant cell astrocytoma (SEGA), which is a rare, benign childhood neoplasm of grade I histological malignancy according to the WHO classification (WHO GI). SEGA tumours occur in approximately 10-20% of patients with tuberous sclerosis complex (TSC), which is a rare genetic condition [15,82].…”
Section: Introductionmentioning
confidence: 99%